PTH-083 Impact of hospitalisation rate for HCV related liver diseases in north of italy. (8th June 2018) - Caroli, Diego; Rosa-Rizzotto, Erik; Saia, Mario; Scribano, Laura; Peraro, Laura; Lobello, Salvatore; Lazzari, Franca De
Abstract : Background and aims: Hepatitis C virus (HCV) epidemiological data in Italy is changing due to the decline of iatrogenic aetiology and the persistence of infection in populations at risk. The incidence and the prevalence of HCV disease have dropped following also the massive commitment of physicians to treat all the infected patients. However, all over the world HCV liver-related disease is the first cause of hospital admission in patients with liver diseases. We analysed the trend of hospitalisation for liver HCV-related disease in Veneto Region, North East Italy, from 2000 to 2016, in order to report the impact of HCV treatment with different therapeutic schedules. Method: This is a retrospective cohort study based on Veneto Region anonymous computerised database of hospital discharges between 2000 and 2016. All Veneto residents discharge records with principal diagnosis of hepatitis (cod. ICD9-CM: 070.41, 070.44, 070.51, 070.54, 070.70, 070.71, 571.5, 571.9) were included in the study. We chose the principal diagnosis because it is considered the primary reason for hospital admission. The Standardised Hospitalisation Ratio (SHR) per five-year age group (ref. pop. Veneto 2008) was calculated and expressed per 100 000 population. Results: In the period considered 36 102 hospital admissions diagnosed with HCV have been recorded. Approximately half of patients were males (56%). Despite their lower age (56, 1±7, 2 Vs. 65, 1±8, 3), they had the greatest hospitalisation rate (51, 4 Vs. 37, 9; OR:1.36;CI95%:1.33–1.39;p<0.05).The analysis of the hospitalisation trend shows a 14% increase in the average age of patients(from 57, 3±9, 5 to 65, 1±9, 9) and a substantial decrease in hospital admissions (X2 trend: 9210, 736; p<0, 05). Between 2000 and 2016, there has been a 81% decline in hospital admissions (i.e. from 78, 9 to 14, 8) with a comparable decrease in both genders/sexes (ratio M:F 1.5). In 2012–2014 period we observed a plateau in the curve while in 2015–2016 the decline starts again (figure 1). Conclusion: HCV liver-related disease as cause of hospital admission is in progressive and constant decline related to the different treatment schedules available in each period. Moreover this downward trend reflects the improvement in management of advanced liver disease in outpatient settings. In the last two yrs of observation the decline starts again because of the availability of DAAs with high efficacy also in patients with advanced stage of liver disease.